Condensation of nitromethane with dialdehydes. - Achmatowicz, Barbara. (University of Ottawa (Canada), 1963)
Phthalaldehyde was found to react with nitro-methane, in methanolic solution and in the presence of sodium methoxide, to give the sodium salt of 2-aci-nitro-indandiol-1,3. It was found that this salt, on acidification with ion exchange resin, afforded a mixture of 2-nitro-indandiol-1,3 and 2-nitroindenol-3, which were separated by fractional crystallisation. The structures of the compounds obtained were established by nuclear magnetic resonance spectroscopy. Hence, the applicability of phthalaldehyde in the condensation with nitromethane, to form a five-membered carbocyclic ring, was nitromethane, to form a five-membered carbocyclic ring, was shown. On the other hand, when the reaction between phthalaldehyde and nitromethane was carried out without solvent, in the presence of sodium carbonate, the hemiacetal of 2-(1-hydroxy-2-nitroethyl)-benzaldehyde was exclusively formed. The structure of the latter was proved by means of chemical transformations leading to the isoquinoline system. For the study concerning the closure of a seven-membered ring, adipic aldehyde was chosen. Under all conditions investigated, no formation of a seven-membered carbo-cyclic ring was noticed. It is believed that the failure was due to a more rapid formation of other compounds, namely 1,8-dinitrooctane-2,7-diol and the product of internal aldol condensation of adipic aldehyde, cyclopentene-1-aldehyde.
Keywords: Chemistry, Organic.